Defining human-machine micro-task workflows for constitution making - Luz, Nuno Miguel Almeida (2015)
This paper presents a novel task-oriented approach to crowdsource the drafting of a constitution. By considering micro-tasking as a particular form of crowdsourcing, it defines a workflow-based approach based on Onto2Flow, an ontology that models the basic concepts and roles to represent workflow-definitions. The approach is then applied to a prototype platform for constitution-making where human workers are requested to contribute to a set of tasks. The paper concludes by discussing previous approaches to participatory constitution-making and identifying areas for future work.